Bacterial and fungal diversities examined through high-throughput sequencing in response to lead contamination of tea garden soil - Zhang, Ziyan; Deng, Qingmei; Ye, Hui; Ge, Gaofei (Frontiers in Microbiology, 2023)
Several studies have indicated that the heavy metal content in tea is increasing gradually. Researchers examining the soil of more than 100 tea gardens in China have observed that lead content was higher in some soils. The effect of lead contamination on soil microorganisms in tea gardens was studied to determine the effect of lead on the essential functions of microorganisms in a tea garden soil ecosystem. Previous studies on pot experiments adopted the method of adding a single instance of pollution, which failed to comprehensively simulate the characteristics of the slow accumulation of heavy metals in soil. This study designed with two pollution modes (multistage and single instance) determined the content of soil lead in different forms according to the European Community Bureau of Reference extraction procedure. The community structure, species diversity, and functional abundance of soil bacteria and fungi were examined by high-throughput sequencing. We observed that the content of four forms of lead was higher in the multistage contamination mode than in the single instance contamination mode. The effects of lead contamination on bacteria differed significantly (P < 0.05), and the abundance and diversity of bacteria were higher in the multistage contamination mode than in the single instance contamination mode. The community structure of fungi was more affected by lead than was that of bacteria. The content of each lead form was the environmental factor most strongly affecting soil bacteria and fungi. The predicted main function of the bacterial community was amino acid transport and metabolism, and the trophic mode of the fungal community was mainly pathotroph–saprotroph. This study revealed changes in soil microorganisms caused by different forms of lead and contamination methods in tea garden soil and provide a theoretical basis for examining the effects of lead contamination on soil microorganisms.